Influence of yttrium addition on reactive sputtered W–Y–N coatings. (3rd August 2017) - Ye, F.; Zhao, L.; Mu, C.; Zhao, H.
Abstract : W–Y–N coatings with yttrium content ranging from 0 to 8.2 at.-% were deposited by reactive magnetron sputtering technique. The influence of yttrium content on the structure, oxidation resistance and mechanical properties was investigated. The results show that yttrium atoms substitute tungsten atoms forming the solid solution W–Y–N coatings. All the coatings exhibit a single-phase face-centered cubic structure and the preferred orientation changes from (200) to (111) with yttrium addition. The grain size of W–Y–N coatings decreases with the increase of yttrium content. The oxidation resistance temperature of W–Y–N coatings increases from 500°C at 0 at.-% Y to 730°C at 8.2 at.-% Y. All coatings are in compressive stress state. The hardness, elastic modulus and compressive stress of W–Y–N coatings increase gradually from 28.0, 320 and 1.1 GPa at 0 at.-% Y to 36.0, 385 and 2.1 GPa at 8.2 at.% Y, respectively. The improvement of hardness was attributed to the effect of solid solution strengthening and the grain refinement. In addition, the addition of yttrium content into WN coating also improves its resistance against elastic strain and plastic deformation to failure.